Serum 25-hyroxyvitamin D levels and tic severity in Chinese children with tic disorders. (September 2018) - Li, Hong-Hua; Shan, Ling; Wang, Bing; Du, Lin; Xu, Zhi-Da; Jia, Fei-Yong
Highlights: Vitamin D deficiency might be associated with tic disorders. The relationships among serum 25(OH)D level, the risk of developing tics, and tic severity have not been investigated in children with tic disorders. Our data support an association between low serum 25(OH)D level and increased odds of tic disorder diagnosis in children. Large sample size studies are urgently needed to further clarify the correlation between serum 25(OH)D level and tic severity. Whether vitamin D supplementation should be considered as a potential treatment in children with tic disorders, especially those with vitamin D insufficiency or deficiency, needs further investigation. Abstract: The aim of this study is to evaluate serum 25-hydroxyvitamin D[25(OH)D] levels in children with tic disorders and to explore the relationship between serum 25(OH)D level and tic severity. Children ( n = 179, 31 females, 148 males, mean age at diagnosis: 8.0 ± 2.7 years old, age ranged from 3 to 14.5 years old) who were diagnosed with a tic disorder were enrolled as case group, 189 healthy children were recruited as control group. Serum level of 25(OH)D of each child was measured by high performance liquid chromatography and tandem mass spectrometry (HPLC-MS/MS). Yale Global Tic Severity Scale (YGTSS) was used to assess tic severity. Mean serum level of 25(OH)D in the case group was significantly lower than that of the control group. The serum 25(OH)D level was significantly associated with tic severity after adjusting for age and body mass index (BMI). This study identified a high prevalence of vitamin D insufficiency or deficiency in children with tic disorders, and there was a negative correlation between the serum 25(OH)D level and tic severity. In the future, large sample size studies are urgently needed to further clarify this correlation.